Tai Chi exercise improves working memory capacity and emotion regulation ability - Wang, Yi; Tian, Jing; Yang, Qingxuan (Frontiers in Psychology, 2023)
Purpose: The study aimed to research the promoting effects of Tai Chi exercise on working memory capacity and emotional regulation ability among college students. Methods: 55 participants were recruited and randomly divided into the Tai Chi group and control group. The Tai Chi group had a 12-week Tai Chi training to implement intervention, while the control group performed non-cognitive traditional sports with the same intensity of the Tai Chi group. The visual 2-back test of action pictures and the Geneva emotional picture system test were performed before and after the experiment, which aimed to examine whether the action memory of Tai Chi training can improve individuals’ working memory capacity and emotion regulation ability. Results: The results of the working memory revealed a Significant effects in Time (F=98.662, P≤0.001), Group (F=21.435, P≤0.001), and Interaction (Groups × time) (F=50.815, P≤0.001) on Accuracy Rate (AR) of the Visual Memory Capacity were observed. The same effect was observed again on the Response Time of the Visual Memory Capacity, Time(F=67.211, P≤0.000, Group (F=45.685, P≤0.001 ), Interaction (groups × time) (F=79.526, P≤0.001). Analysis of the emotional fluctuations revealed that The effect of valence differences in Time (F=6.98, P<0.05), Group (F=4.83, P<0.05), and Time*Group (F=10.78, P<0.01), respectively, was significant in the Tai Chi group after 12- week intervention. The effect of arousal difference in Time (F=5.08, P<0.05), Group (F=8.82, P<0.01), Time*Group (F=4.15, P<0.05), respectively, was significant in the Tai Chi group after 12-week intervention. As the same, the effect of dominance differences in Time (F=6.43, P<0.05), Group (F=6.74, P<0.05) and Time*Group (F=15.19, P<0.001), respectively were significantly in the Tai Chi group. Conclusion: Tai Chi exercise practice can improve an individual’s working memory mapacity and emotion regulation capacity. Action memory training improves emotion regulation ability, which has provided insightful information for customized exercise programs for emotional regulation in adolescents. Adolescents who are experiencing volatile moods and poor emotion regulation should take Tai Chi classes regularly, which could contribute to emotional health.